TATHBIQU I’DADI BUNUDI AL-IKHTIBARI LI MAHARAH AL-ISTIMA’ WA AL-KALAM - Renni Hasibuan; Dewi Chamidah; Akhsan Akhsan (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
Preparing test items is an important step in developing an educational curriculum. However, teachers usually do not take it seriously regarding the implementation of the preparation of these items, so that compiling assessment tools in evaluation has not carried out the steps for developing the tools as they should, namely improving the items. Therefore, the preparation and development of instruments is an important thing that influences the decision making of learning assessment results. The purpose of writing this article is to describe steps and application of the preparation of items to measure good listening and speaking skills. This research uses a qualitative approach with the type of library research. As for data collection techniques based on reading results as well as books, journals and documents related to the theme of this article. The items designed for class XII Madrasah Aliyah with the topic